Continuously differentiable solutions of one boundary value problem for a systems of linear difference differential equations of neutral type - Vel'hach, A.V. (Carpathian Mathematical Publications, 2015)
Conditions of the existence of continuously differentiable bounded for tR^+ solutions of one boundary value problem for a systems of linear and nonlinear difference differential equations of neutral type have been obtained, the method of their construction has been developed and investigate the asymptotic properties of these solutions.